UM ESTUDO SOBRE O PROGRAMA LER E ESCREVER DA REDE PÚBLICA DO ESTADO DE SÃO PAULO - Camacho, Priscila Vita (2010)
The objective of this project is analyse the Read and Write Program of state schools from São Paulo to argue their theorist system elements. The project Read and Write represents one more try from public teaching system on the way to revert the unstable situation presented by students from public schools on the read and write process. The second chapter presents the legislation that endorses the program and also the way how has been applied. The third chapter presents the methodological procedure. Questionnaires had been developed for teachers and elaborated points of analysis to classify depositions from the reports by dialectics categories of theorist system referential made by Alves (2000). Some interviewed teachers believe that the program brings new ideas, however the theoretical referential is based on constructivism that guides the Brazilian education institutional documents for more than 25 years.(AU)